Use and Sustainability of Miombo Woodlands under Community Management in Zimbabwe (Nordic Journal of African Studies, 2000)
The use and sustainability of miombo woodlands under community management was studied in north eastern Zimbabwe using Participatory Rural Appraisal (PRA) methods. The study especially focussed on benefits obtained from miombo woodlands, their seasonal variability and long-term changes of woodland resources in the Mangwende communal area so as to assess the sustainability of communal management of forest land in the study area.Like farmers everywhere in Southern Africa, people in the study region are largely dependent on resources found on communal and state owned lands. In the study area, communal woodlands were found to provide a large variety of benefits for local people, especially important during dry seasons, e.g. poles, fibre and thatching grasses, firewood, fodder and traditional medicines. Despite the rich variety of products, the availability of woodland resources has dramatically diminished during the last 30 years. This trend, which is expected to continue, has forced people to use manufactured substitutes, e.g. for medicinal, nutritional and heating purposes. Most of the few forested areas left in the region are heavily degraded, but still continuously under over-utilisation.Based on the collected data, it was evident that community management has not helped the environment to survive the increased land use pressure brought about by a growing population in the study area. It is, however, too simplistic to assume that community management has directly caused environmental degradation. In the case of forest cover loss, for example, population pressure has probably been a bigger reason for deforestation than failures in land management.